Cranial morphology of embrithosaurus schwarzi (Parareptilia, Pareiasauria) and a taxonomic and stratigraphic reassessment of the South African Middle Permian Pareiasaurs - Van den Brandt, Marc Johan (My University, 2017)
Pareiasaurs were abundant, large, herbivorous parareptiles of the middle and late Permian which had a global distribution. The most basal pareiasaurs are found only in the middle Permian of South Africa, suggesting a Gondwanan origin for the group. Despite their relative abundance, most pareiasaurs are poorly known, especially the large middle Permian South African taxa that went extinct at the end of the Tapinocephalus Assemblage Zone. Historic taxonomic confusion was reduced with studies by Lee (1995, 1997a) that addressed the alpha-taxonomy of all pareiasaurs. He reduced the middle Permian South African pareiasaurs from 11 to four species: Bradysaurus baini, B. seeleyi, Embrithosaurus schwarzi and Nochelesaurus alexanderi. However this revision did not include detailed anatomical descriptions of any of the middle Permian South African Tapinocephalus Assemblage Zone taxa. The first detailed cranial description of Embrithosaurus schwarzi is presented in this contribution. Within the middle Permian pareiasaurians, Embrithosaurus has unique wide, short and stubby teeth with nine marginal cusps arranged more regularly. A cranial taxonomic reassessment of all middle Permian pareiasaurs has confirmed the validity of the four taxa identified by Lee and produced updated cranial diagnoses for each species. Diagnostic features noted by Lee and retained include an autapomorphic large distinctive maxillary boss on a strongly buckled or bent maxilla for B. baini, distinctive horizontally flat and pointed bosses on the posterior margin of the quadratojugal for Nochelesaurus and the smallest cheek flanges for B. seeleyi. Using the updated diagnoses, re-identification of 39 specimens out of 108 studied has produced updated biostratigraphic ranges for the middle Permian species. B. seeleyi is the first to make an appearance, in the middle Koornplaats Member of the Abrahamskraal Formation. B. baini first appears in the upper iii Koornplaats Member, Nochelesaurus in the Swaerskraal Member, and Embrithosaurus in the lower Moordenaars Member of the Abrahamskraal Formation. All taxa disappear by the top of the Karelskraal Member of the Abrahamskraal Formation, confirming that all the middle Permian pareiasaur species went extinct at the end of the Tapinocephalus Assemblage Zone.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the Degree of Master of Science. Johannesburg, 2016.
Keywords: Paleontology--South Africa--Karoo; Geology, Stratigraphic--South Africa--Karoo; Therapsida--South Africa